2020
DOI: 10.1016/j.ypmed.2020.106067
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of universal multiple-risk lifestyle interventions in reducing depressive symptoms: Systematic review and meta-analysis

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 90 publications
(281 reference statements)
4
21
0
Order By: Relevance
“…Encouragingly, no adverse effects resulting from the LM intervention were reported in this study. In line with the meta-analysis and recent RCTs, we showed that LM interventions were superior to CAU in managing depressive symptoms [33][34][35][36][37]56].…”
Section: Discussionsupporting
confidence: 86%
“…Encouragingly, no adverse effects resulting from the LM intervention were reported in this study. In line with the meta-analysis and recent RCTs, we showed that LM interventions were superior to CAU in managing depressive symptoms [33][34][35][36][37]56].…”
Section: Discussionsupporting
confidence: 86%
“…EIRA was a health promotion intervention designed following Medical Research Council methodology [ 13 ] (including systematic reviews [ 14 22 ], citizen and professional participation through qualitative research [ 23 25 ] and a previous pilot study, among other techniques) and was based on the Transtheoretical Model [ 26 ]. Physicians and nurses applied the intervention in their routine practice in the PHC centre.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in the study of the multiple lifestyle interventions on depressive symptomatology, and the results are promising [ 18 , 19 , 20 ]. A recent meta-analysis suggested that universal multiple-risk lifestyle interventions may produce a modest but statistically significant effect decreasing depressive symptomatology in adults, although the available evidence base is still low [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in the study of the multiple lifestyle interventions on depressive symptomatology, and the results are promising [ 18 , 19 , 20 ]. A recent meta-analysis suggested that universal multiple-risk lifestyle interventions may produce a modest but statistically significant effect decreasing depressive symptomatology in adults, although the available evidence base is still low [ 18 ]. These findings are supported by another recent meta-analysis, which concluded that multicomponent lifestyle medicine interventions may be effective reducing depressive symptomatology at short-term follow-up [ 19 ].…”
Section: Introductionmentioning
confidence: 99%